NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERITA RAKYAT NUSANTARA DARING DAN RELEVANSINYA TERHADAP MATERI PEMBELAJARAN TEKS NARATIF DI SMA - Luh Putu Diah Vigayanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The selection of literary works as teaching materials is difficult for an educator/teacher. Teachers have to consider the criteria of 'validity' and 'suitability' in sorting and selecting literary works. This study aims to find forms of character education values in eight Indonesian legends from the BRITISH COURSE website. In addition, the eight stories are sought for relevance to narrative text material in SMA N 1 Nusa Penida.The research subjects were eight short stories in English and Indonesian. They were collected using documentation and observation methods.All stories were read and filtered using note-taking and elicitation techniques. Stories that meet the criteria of validity and suitability are recorded in the checklist while the rest will be elicited. The data were analyzed descriptively with three working steps: coding, categorizing, describing and interpreting. Coding is given to the title to be analyzed with abbreviations. Next, the data is grouped by character value. Finally, the data is described and interpreted. The results of this study indicate that eight folk tales from the archipelago are determined, namely: ((1) The Legend of Catu Island, (2) The Little Sawah, (3) The Legend of Pesut Mahakam, (3) The Legend of Belumbak Island, (4) The Legend of Singaraja, (5) The Legend of Telaga Warna, dan (6) The Legend of Situ Bagendit. The eight legends contain validity criteria, such as: (a) six values of character education: the value of hard work, the value of social care, the value of honesty, the value of religious, the value of love of peace, and the value of independence; (b) interesting and useful, and (d) easy to reach because it is presented online. Suitability criteria, the legends (a) use English and Indonesian which is not too difficult, (b) is in line with the socio-cultural environment because it is in the form of Indonesian folklore, (c) according to age, interests, psychological development, and (d) fostering curiosity.Keywords: character values, legend, narrative prose